2018
DOI: 10.1159/000493964
|View full text |Cite
|
Sign up to set email alerts
|

miR-449a Suppresses Tamoxifen Resistance in Human Breast Cancer Cells by Targeting ADAM22

Abstract: Background/Aims: Most of estrogen receptor positive breast cancer patients respond well initially to endocrine therapies, but often develop resistance during treatment with selective estrogen receptor modulators (SERMs) such as tamoxifen. Altered expression and functions of microRNAs (miRNAs) have been reportedly associated with tamoxifen resistance. Thus, it is necessary to further elucidate the function and mechanism of miRNAs in tamoxifen resistance. Methods: Tamoxifen sensitivity was validated by using Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…23 miR-449a inhibits tamoxifen resistance of human breast cancer cells via targeting ADAM22. 24 miR-449a hinders tumor F I G U R E 4 SNHG7 upregulates ACSL1 through sequestering miR-449a in TC cells. A, After transfection, RT-qPCR was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…23 miR-449a inhibits tamoxifen resistance of human breast cancer cells via targeting ADAM22. 24 miR-449a hinders tumor F I G U R E 4 SNHG7 upregulates ACSL1 through sequestering miR-449a in TC cells. A, After transfection, RT-qPCR was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…TFPIa is an apoptosis inducer in BC cells . A decrease in exosomal miRNA‐449a of BC cells upregulates the expression of ADAM22 (a disintegrin and metalloprotease domain‐22) and, thereby, induces the tamoxifen resistance …”
Section: Exosomal Mirnas In Bc Drug Resistancementioning
confidence: 99%
“…Furthermore, miR‐449a served as diverse role in diversified diseases and cells. For example, miR‐449a was explored to play essential role in breast cancer endocrine resistance . Another research demonstrated that inhibition of miR‐449a prevented H9c2 cells from hypoxic injury via Notch‐1 pathway .…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-449a was explored to play essential role in breast cancer endocrine resistance. 22 Another research demonstrated that inhibition of miR-449a prevented H9c2 cells from hypoxic injury via Notch-1 pathway. 23 Currently, we proposed to investigate circ-Ttc3 and miR-449a influence and interaction mechanism in HaCaT cells.…”
mentioning
confidence: 99%